2019
DOI: 10.21079/11681/33619
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sand boils near Ware, IL, Middle Mississippi River, Preston Levee District

Abstract: During flooding in 2011, 2013, and 2016 on the Middle Mississippi River between St. Louis and Cape Girardeau, MO, high-energy sand boils developed at the land side levee toe. These recent floods varied from moderate to major events but were well below the design flow line for the levees. This report documents a case study of internal erosion at a levee site in southern Illinois near the town of Ware, which is located in the Preston Drainage and Levee District. Site specific geotechnical data from the Ware site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In this case, thus, the flood event did not induce any uplift effect at the toe, with the development of new cracks within the top stratum; rather, the piping activity observed therein is very likely to be attributed to the reactivation of a pre-existing sand boil, that can be triggered by lower local gradients. Indeed, as also observed by Kelley et al [9] for to the Mississippi River, in chronic seepage areas, sand boil activity can form at lower levels of flooding because of the accumulated effects of internal erosion at these locations. The effect of a pre-eroded soil volume on the initiation of piping has been also investigated by García Martínez et al [36] using an FE approach, with reference to a well-documented cross-section of the Po River close to the delta.…”
Section: Application Of Simplified Methods To Assess Piping Susceptib...supporting
confidence: 61%
See 3 more Smart Citations
“…In this case, thus, the flood event did not induce any uplift effect at the toe, with the development of new cracks within the top stratum; rather, the piping activity observed therein is very likely to be attributed to the reactivation of a pre-existing sand boil, that can be triggered by lower local gradients. Indeed, as also observed by Kelley et al [9] for to the Mississippi River, in chronic seepage areas, sand boil activity can form at lower levels of flooding because of the accumulated effects of internal erosion at these locations. The effect of a pre-eroded soil volume on the initiation of piping has been also investigated by García Martínez et al [36] using an FE approach, with reference to a well-documented cross-section of the Po River close to the delta.…”
Section: Application Of Simplified Methods To Assess Piping Susceptib...supporting
confidence: 61%
“…All sand boils are typically monitored on site "manually", by technicians of AIPo who are in charge of surveying critical cross-sections, detecting sand boil activations/reactivations during high-water events and implementing emergency actions to stop erosion progression, whenever necessary. In this respect, it must be observed that the growing need for an accurate, possibly automated identification of surface evidence of backward erosion piping worldwide has encouraged in recent years the application of sophisticated techniques, such as satellite or drone imagery together with machine learning models (e.g., [9,22,42]), which are meant to facilitate capturing sand boil activity and local predisposing conditions. necessary.…”
Section: Database Structurementioning
confidence: 99%
See 2 more Smart Citations